The Role of the Intelkam Unit's Investigation on Motor Vehicle Theft in Assisting the Investigation Process at Karawang Police - Barky, Ronal (Police Studies Review, 2024)
The focus of this study is the high crime of motor vehicle theft in the Karawang regency. The Karawang Regional Police Intelligence Unit has a role as an investigator in the case of fraud. The purpose of this thesis research is to describe the description of examples of motor vehicle theft in the jurisdiction of the Karawang Police Station, describe the role of intelligence unit investigations on motor vehicle theft in assisting the investigation process at the Karawang Regional Police Station, as well as explain what factors influence the investigation role of intelligence units on vehicle theft motorized in helping the investigation process at Karawang Regional Police Station To analyze the problem, the writer uses the field and research method with a qualitative approach. This type of research is descriptive-analytic. Primary and secondary data sources. Data collection techniques with interviews, observation, and document review. The validity of triangulation. Data analysis. Theories and concepts used are role theory, inquiry theory, management theory, and MOPI theory. The results of data analysis from the research findings, the phenomenon of investigation of the occurrence of fraud that occurred in the Karawang regency by the intelligence unit refers to management theory, in analyzing the role of the intelligence unit in the investigation process using the role theory and the concept of operational intelligence management or MOPI. The conclusion that can be drawn is the high number of cases of fraud in the Karawang region caused by the economic and lifestyle factors of the Karawang community itself. The role of the Karawang Regional Police Intelligence Unit is to map vulnerable areas and investigate cases of fraud that occur to be reported and be considered by the leadership in making further policies. Some factors influence the role of intelligence units. Suggestions given by the authors include increasing motivation and quality of members and growing community raising.